MATHEMATICAL THINKING IS A SUBJECT OF PSYCHOLOGICAL STUDY - Мойсеєнко, Л. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article there have been pointed out the specific manifestations of thinking – mathematics, which is connected with application of mathematical symbolism, formalized model of investigated processes, parallel existence of axiomatic and constructive methods for developing mathematical theories and availability of algorithms for solving many mathematical problems. Psychological study analysis of mathematical thinking gives the right to assert that they are differential (differented) and, as a result, there is no integral psychology characteristic of mathematical thinking; there has not been investigated its procedural-dynamic aspect; there have not been brought to light the peculiarities of searching process in solving creative mathematical problems.